Soluble guanylate cyclase mediates the relaxation of healthy and inflamed bladder smooth muscle by aqueous nitric oxide - Aronsson, Patrik; Stenqvist, Johanna; Ferizovic, Ena; Danielsson, Emelie; Jensen, Anna; Simonsen, Ulf; Winder, Michael (Frontiers in Physiology, 2023)
Due to its chemical properties, functional responses to nitric oxide (NO) are often difficult to examine. In the present study, we established a method to produce NO in an aqueous solution and validated its capacity to evoke functional responses in isolated rat bladders. Furthermore, we compared the NO responses to the commonly used NO donor sodium nitroprusside (SNP). We also investigated the impact of ongoing inflammation on the involvement of soluble guanylate cyclase (sGC) dependent signaling in NO relaxation.A setup to produce an aqueous NO solution was established, allowing the production of an aqueous solution containing a calculated NO concentration of 2mM. Sixty male Sprague-Dawley rats received either no treatment (controls) or cyclophosphamide (CYP; 100mg*kg-1 i.p., 60hrs prior to the experiment) to induce experimental cystitis. Bladder strip preparations were mounted in organ baths and studied at basal tension or pre-contracted with methacholine (3μM). Aqueous NO solution (40-400µL; 2mM corresponding to 4-40μM) or SNP (1-1000μM) was added cumulatively in increasing concentrations. Relaxation to aqueous NO was also studied in the presence of the sGC inhibitor ODQ (0.25-25μM). The expression of sGC was investigated by immunohistochemical analysis.The NO solution caused functional relaxations in both controls and inflamed bladder preparations. NOinduced relaxations were significantly greater in inflamed bladder strips at basal tension, whereas no differences were seen in methacholine pre-contracted strips.In the presence of the sGC inhibitor ODQ in a high concentration, the NO-evoked relaxations were abolished in both control and inflamed preparations. At a lower concentration of ODQ, only NO relaxations in inflamed preparations were attenuated.Immunohistochemical analysis showed that sGC was expressed in the detrusor and mucosa, with a significantly lower expression in the inflamed detrusor.In the present study, we found that aqueous NO solution induces relaxation of the rat detrusor by activating soluble guanylate cyclase in both control and inflamed bladder strips. Induction of inflammation conceivably leads to decreased sGC expression in the detrusor, which may explain the different susceptibility towards inhibition of sGC in inflamed versus control tissue.The use of an aqueous NO solution should be further considered as a valuable complement to the pharmacological tools currently used.